Geographical Patterns of Functional Diversity of South American Anurans - Vasconcelos, Tiago S. [UNESP]; Silva, Fernando R. da; Santos, Tiago G. dos; Prado, Vitor H. M.; Provete, Diogo B.; Vasconcelos, TS; DaSilva, FR; DosSantos, TG; Prado, VHM; Provete, DB (Springer, 2019)
A critical step in designing efficient spatial prioritization plans is to find the best network of sites that preserve multiple biodiversity facets. Conservation biogeography has increasingly been using functional diversity (FD) as an alternative metric to describe how trait diversity is distributed throughout space. FD can be promptly related to the function played by species in a community, better than taxonomic diversity. Here, we mapped multiple dimensions of functional diversity of South American anurans that describe functional richness (FRich), evenness (FEve), dispersion (FDis), and rarity (Frar) at the regional scale, as well as geographical restrictiveness and body size. FRich was higher in the Amazon basin, Guianas, Tropical Andes, and the central portion of the Atlantic Forest, whereas lower values appear in Patagonia and the Atacama Desert. FEve and FDis were homogeneously distributed throughout the continent, with lowest values in southern Patagonia, Pacific slope of the southern Tropical Andes, and Atacama Desert, while the highest values were found in the Atlantic slope of the southern Tropical Andes. Patterns of functional distinctiveness and uniqueness were similar and highlighted northwestern Argentina and areas with many endemic and functionally unique species. Frar at the regional scale highlighted the Andes, Patagonia, and the Atlantic Forest.
Keywords: Body size; Functional biogeography; Functional rarity; Life-history traits; Conservation biogeography; South America